SDSS IV MaNGA: bar pattern speed in Milky Way analogue galaxies. Issue 4 (26th October 2022) - Garma-Oehmichen, L; Hernández-Toledo, H; Aquino-Ortíz, E; Martinez-Medina, L; Puerari, I; Cano-Díaz, M; Valenzuela, O; Vázquez-Mata, J A; Géron, T; Martínez-Vázquez, L A; Lane, R
ABSTRACT: Most secular effects produced by stellar bars strongly depend on the pattern speed. Unfortunately, it is also the most difficult observational parameter to estimate. In this work, we measured the bar pattern speed of 97 Milky-Way analogue galaxies from the MaNGA survey using the Tremaine–Weinberg method. The sample was selected by constraining the stellar mass and morphological type. We improve our measurements by weighting three independent estimates of the disc position angle. To recover the disc rotation curve, we fit a kinematic model to the H α velocity maps correcting for the non-circular motions produced by the bar. The complete sample has a smooth distribution of the bar pattern speed ($Ω _{\rm Bar}=28.14^{+12.30}_{-9.55}$ km s −1 kpc −1 ), corotation radius ($R_{CR} = 7.82^{+3.99}_{-2.96}$ kpc), and the rotation rate ($\mathcal {R} = 1.35^{+0.60}_{-0.40}$ ). We found two sets of correlations: (i) between the bar pattern speed, the bar length and the logarithmic stellar mass (ii) between the bar pattern speed, the disc circular velocity and the bar rotation rate. If we constrain our sample by inclination within 30° < i < 60° and relative orientation 20° < |PAdisc − PAbar | < 70°, the correlations become stronger and the fraction of ultra-fast bars is reduced from 20 to 10 per cent of the sample. This suggests that a significant fraction of ultra-fast bars in our sample could be associated with the geometric limitations of the TW method. By further constraining the bar size and disc circular velocity, we obtain a subsample of 25 Milky-Way analogues galaxies with distributions $Ω _{\rm Bar}=30.48^{+10.94}_{-6.57}$ km s −1 kpc −1, $R_{\rm CR} = 6.77^{+2.32}_{-1.91}$ kpc, and $\mathcal {R} = 1.45^{+0.57}_{-0.43}$, in good agreement with the current estimations for our Galaxy.